Quackery in Dental Practice in Nepal - Humagain, Manoj (JNMA J Nepal Med Assoc, 2020)
Quackery and fraud in dental practice, seen in many countries, is also rampant in Nepal, and they are unethical practices. There is a growing need for strict enforcement of government policy measures to eliminate quackery and fraudulent dental practice in Nepal. The government should mobilize all dental workforce (dental specialists, dentists, and dental auxiliaries) and aware of their responsibilities and limitations. This article presents a brief review showing some cases of malpractice in dentistry in Nepal.